Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pelanggan Ahass Daya Motor Surabaya - Syamsul Arifin; Nur Aini Anisa; Priyo Utomo (Journal on Education, 2023)
This study aims to describe the analysis of customer satisfaction at AHASS Daya Motor in 2020-2021. The data collection technique used is the documentation technique. The data analysis technique used is quantitative descriptive analysis technique. The result of this marketing strategy research are based on four main elements, namely product, price, place, promotion which are determined to be successful. The theory of customer behavior consists of four theories, namely microeconomic theory, psychological theory, sociological theory, and anthropological theory. The factors influencing service quality consist of tangible, reability, responsiveness, assurance, empathy. Benefits provided to customers by trying to understand consumers desires. So that each company is expected to have understanding and knowledge about customers, understand customer needs specifically, and have comfortable operating times for customers.